Art incarnating an act of ethnic resistance and transcending national boundaries : Allen Sapp - Weretiuk, Oksana (2020)
The essay aims to discuss the notion that Aboriginal people, by their mere existence, incarnate an act of resistance. Continuing to live, despite the 19th-century Canadian policy that wanted them to die out and disappear, they kept their ethnicity, and even when adopting the dominant group's culture they present a unique cultural space in Canada. Among those who have drawn their artistic inspirations directly from Aboriginal community and folk art is Allen Sapp (1928–2015), a Canadian Cree painter who resided in North Battleford. He was one of the first Canadian Indigenous artists to enjoy international acclaim. Sapp recorded the everyday lives and festivities of the Cree and other prairie peoples, and that could be read as a form of ethnic resistance. On the other hand, Allen Sapp absorbed the artistic achievements of the European school, creating Canadian art which transcends the national boundaries of his ethnic community. L'article vise à discuter de la notion selon laquelle, par leur existence, les peuples autochtones incarnent un acte de résistance. Continuant à vivre, malgré la politique canadienne du XIXe siècle qui voulait qu'ils s'éteignent et disparaissent, ils ont conservé leur appartenance ethnique et, même en adoptant la culture du groupe dominant, ils continuent à présenter un espace culturel unique au Canada. Parmi ceux qui ont tiré leurs inspirations artistiques directement de la communauté autochtone et de l'art populaire, il y a Allen Sapp (1928–2015). Il a été l'un des premiers artistes autochtones du Canada à bénéficier d'une renommée internationale. Sapp a enregistré la vie quotidienne et les festivités des Cris et d'autres peuples des Prairies, ce qui pourrait être interprété comme une forme de résistance ethnique. D'autre part, Allen Sapp a absorbé les réalisations artistiques de l'école européenne, créant un art canadien qui transcende les frontières nationales de sa communauté ethnique.